La compra de bienes y el gasto en sueldos y salarios en los resultados de operación de la empresa Electro Oriente S.A. periodo 2015 - 2019 - Marín Eléspuru, César Ulíses (2021)
Electro Oriente S.A. is dedicated to producing, distributing and commercializing electrical energy in Loreto and other regions, for which it must necessarily incur costs and expenses. The objective of this thesis was to determine the influence of the purchase of goods and the expenditure on wages and salaries on the operating results of the company Electro Oriente SA, in the period 2015 - 2019. For this, this research was carried out on Quantitative type, Correlational level and Non-Experimental design. The research concludes that the purchase of goods inversely influences the operating results, since the statistical test shows that the Correlation Coefficient, which was r = -0.897924765; and the Coefficient of Determination was R2 = 0.806268884. However, the expenses in wages and salaries are not related to the operating results, since the Correlation Coefficient was r = -0.571656944; and the Coefficient of Determination was R2 = 0.326791662. The acquisition of inputs and supplies accounted for 90.63% of the purchase of goods, amounting to S /. 1,362,044,230.00. Salaries and salaries expenses had a growing positive evolution during the investigation period that was 7.93% on average per year, meaning the value of S /. 26,752,273.00 on average per year. Likewise, the operating results had a variable behavior of S /. 75,094,267.00 annual average (-4.18%).